2020
DOI: 10.1590/1980-265x-tce-2018-0488
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Psychoactive Substances by Nursing Workers: An Integrative Review

Abstract: Objective: to analyze the scientific evidence available on the factors and implications related to the use of psychoactive substances by nursing workers. Method: an integrative review, which had the following as selection criteria: primary studies, published between 2008 and 2017, without language restrictions and that included aspects related to the consumption of psychoactive substances by nursing professionals. The bibliographic survey was carried out in the months of September and October 2018, in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
1
1
0
3
Order By: Relevance
“…Predisposing factors for the use of these substances include, in addition to the presence of mental disorders, elements such as the intense workload, precarious working conditions and experiences of suffering, for which the use of these drugs offers psycho-emotional relief. The study also showed that moments of professional or personal crisis demarcated periods in which the use of psychoactive drugs becomes a necessity for these workers (22) , which is in line with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Predisposing factors for the use of these substances include, in addition to the presence of mental disorders, elements such as the intense workload, precarious working conditions and experiences of suffering, for which the use of these drugs offers psycho-emotional relief. The study also showed that moments of professional or personal crisis demarcated periods in which the use of psychoactive drugs becomes a necessity for these workers (22) , which is in line with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Os fatores predisponentes para o uso destas substâncias incluem, além da presença de transtornos mentais, elementos como a intensa carga de trabalho, precarização das condições laborais e vivências de sofrimento, para os quais o uso destes medicamentos oferece alívio psicoemocional. O estudo mostrou também que os momentos de crise profissional ou pessoal demarcam períodos em que o uso de psicoativos passa a ser uma necessidade para esses trabalhadores (22) , o que vai ao encontro dos resultados deste estudo.…”
Section: Discussionunclassified
“…(22) Também, podem emergir desequilíbrios quando estados de tensão, conscientes ou inconscientes se fazem presentes. (20) Nesse sentido, um trabalhador pode vir a desenvolver quadros depressivos, bem como buscar em fármacos e drogas ilícitas ou lícitas, mecanismos de compensação, (23) o que pode trazer prejuízos para sua vida pessoal e profissional. (24) Desse modo, percebe-se que os sujeitos são singulares e precisam que suas necessidades sejam atendidas, (22) sobretudo porque quando se conhece as necessidades dos trabalhadores, estratégias de proteção passam a ser melhor elaboradas, logo há ações mais efetivas.…”
Section: Discussionunclassified